Fairness and Social Risk I: Unaggregated Analyses - Fishburn, Peter C.; Sarin, Rakesh K. (Management Science, 1994)
This paper is the first of a two-paper study of fairness issues for decisions that affect the benefits received and the risks encountered by a population. The study examines fairness for individuals and for homogeneous groups within the population. It considers fairness both for population benefit-risk profiles and for probability distributions over profiles that reflect uncertainty about outcomes of decisions. The present paper focuses on fairness for profiles in which benefits and risks are not aggregated within groups or across the population. It ties fairness to notions of envy among individuals and groups that are based on individuals' preferences. The sequel will discuss aggregation of benefits and risks along with fairness from an aggregated perspective.